Peran Brand Ambassador dan Tagline “Gratis Ongkir” Shopee Terhadap Keputusan Pembelian Shopee Pada Generasi Z di Kota Bandar Lampung - Azahra, Intan Nabila; Putri, Almira Devita (Universitas Sam Ratulangi, 2023)
The research aims to determine whether or not brand ambassadors and taglines in Bandar Lampung City play a role in the buying habits of Generation Z. This research uses a quantitative approach. The respondents of this research are Gen Z in Bandar Lampung City who are Shopee users who have seen and are familiar with the Blackpink brand ambassador and Shopee's